Isolated rectus muscle rupture following trauma - Çağatay, Halil Hüseyin; Ekinci, Metin; Ulusal, Şendoğan; Oba, Mehmet Ersin; Yazar, Zeliha (Nepalese Journal of Ophthalmology, 2016)
Background: Isolated rectus muscle ruptures are rare ophthalmic emergencies which may result in permanent diplopia. Objective: To highlight updates on clinical features, surgical treatment options and potential complications for isolated inferior rectus ruptures. Case: A 39-year-old man came to our emergency department complaining of diplopia and upward deviation of the right eye after experiencing an animal injury. Extraocular movements were limited in the right eye in the downgaze position. The alternate prism and cover test, both at distance and near testing, showed hypertropia of 40 prism diopters (PD) of the right eye. The right eye had periorbital swelling and conjunctival haematoma. An inferior rectus rupture repair was performed under local anesthesia and monitored sedation. Follow-up examination revealed a 20 PD hypertropia, causing diplopia in all gazes. A second surgical intervention was planned six months after the initial surgery, an inferior rectus 6 mm resection was performed, after which orthophoria was achieved in the primary position both at distance and near testing.